Unraveling the Role of Angiogenesis in Cancer Ecosystems - Zuazo-Gaztelu, Iratxe; Casanovas, Oriol (Frontiers in Oncology, 2018)
Activation of the tumor and stromal cell-driven angiogenic program is one of the first requirements in the tumor ecosystem for growth and dissemination. The understanding of the dynamic angiogenic tumor ecosystem has rapidly evolved over the last decades. Beginning with the canonical sprouting angiogenesis, followed by vasculogenesis and intussusception, and finishing with vasculogenic mimicry, the need for different neovascularization mechanisms is further explored. In addition, an overview of the orchestration of angiogenesis within the tumor ecosystem cellular and molecular components is provided. Clinical evidence has demonstrated the effectiveness of traditional vessel-directed anti-angiogenics, stressing on the important role of angiogenesis in tumor establishment, dissemination and growth. Particular focus is placed on the interaction between tumor cells and their surrounding ecosystem, which is now regarded as a promising target for the development of new anti-angiogenics.